Genetic background and microbiome drive susceptibility to epicutaneous sensitization and food allergy in adjuvant-free mouse model - Tereza Hornikova; Anna Jelinkova; Zuzana Jiraskova Zakostelska; Tomas Thon; Stepan Coufal; Andrea Polouckova; Eliska Kopelentova; Miloslav Kverka; Peter Makovicky; Helena Tlaskalova-Hogenova; Anna Sediva; Martin Schwarzer; et al. (Frontiers in Immunology)
BackgroundThe dual allergen exposure hypothesis states that sensitization to food antigens occurs through a damaged skin barrier in individuals with no previous oral tolerance to certain foods. However, the resulting allergic reaction could depend on factors such as the host’s genetic predisposition as well as the skin and gut microbiota.MethodsSpecific-pathogen-free BALB/c and C57BL/6 and germ-free (GF) BALB/c mice were epicutaneously sensitized with ovalbumin (OVA) via dorsal tape-stripped skin and challenged with OVA by intragastric gavage. The development of food allergy (FA) symptoms, the Th2 and mast cell immune response and differences in the skin and gut microbiota were investigated.ResultsBALB/c mice, but not C57BL/6 mice, showed severe clinical signs of FA (hypothermia, diarrhea) as well as a stronger serum antibody response and Th2 cytokine secretion in the spleen and jejunum after OVA-treatment. The increased mast cell count correlated with higher MCPT-1 production and histidine decarboxylase mRNA expression in the jejunum of these mice. The 16S rRNA sequencing analysis revealed lower abundance of short-chain fatty acids producing bacteria in the gut microbiome of OVA-treated BALB/c mice. Changes in the β-diversity of the gut microbiome reflect both the genetic background as well as the OVA treatment of experimental mice. Compared to SPF mice, GF mice developed more severe anaphylactic hypothermia but no diarrhea, although they had a higher mast cell count, increased MCPT-1 production in the jejunum and serum, and increased arachidonate 5-lipoxygenase mRNA expression.ConclusionsWe show that the BALB/c mice are a mouse strain of choice for model of adjuvant-free epicutaneous sensitization through the disrupted skin barrier and following food allergy development. Our results highlight the significant influence of genetic background and microbiota on food allergy susceptibility, emphasizing the complex interplay between these factors in the allergic response.